PERFORMANCE CHARACTERISTICS OF A FRET-BASED IMMUNOASSAY FOR QUANTITATION OF ADALIMUMAB ON A POINT-OF-CARE INSTRUMENT SYSTEM. (21st January 2021) - Ong, Edgar; Huang, Ruo; Kirkland, Richard; Hale, Michael; Mimms, Larry
Abstract: Introduction: A fast (<5 min), time-resolved fluorescence resonance energy transfer (FRET)-based immunoassay was developed for the quantitative detection of adalimumab (ADL) and biosimilars for use in therapeutic drug monitoring using only 20 µL of fingerstick whole blood or serum at the point-of-care. The Procise ADL assay and the ProciseDx analyzer are CE-marked. Studies were performed to characterize analytical performance of the Procise ADL assay on the ProciseDx analyzer. Methods: Analytical testing was performed by spiking known amounts of ADL into negative serum and whole blood specimens. Analytical sensitivity was determined using limiting concentrations of ADL. Linearity was determined by testing ADL across the assay range. Hook effect was assessed at ADL concentrations beyond levels expected to be found within a patient. Testing of assay precision, cross-reactivity and potential interfering substances, and biosimilars was performed. The Procise ADL assay was also compared head-to-head with another CE-marked assay: LISA-TRACKER adalimumab ELISA test (Theradiag, France). The accuracy of the Procise ADL assay is established through calibrators and controls traceable to the WHO 1 st International Standard for Adalimumab (NIBSC code: 17/236). Results: The Procise ADL assay shows a Limit of Blank, Limit of Detection, and Lower Limit of Quantitation (LLoQ) of 0.1, 0.2, and 0.6 µg/mL in serum and 0.5, 0.9, and 1.3 µg/mL in whole blood, respectively. The linear assay range was determined to be 1.3 to 51.5 µg/mL in serum and whole blood. No hook effect was observed at an ADL concentration of 200 µg/mL as the value reported as ">ULoQ". Assay precision testing across 10 days with multiple runs and reagent lots showed an intra-assay coefficient of variation (CV) of 2.8%, an inter-assay CV of ≤1.5%, and a total CV of 3.5%. The presence of potentially interfering/cross-reacting substances showed minimal impact on assay specificity with %bias within ±7.4% of control. Testing of biosimilars (adalimumab-atto and adalimumab-xxxx) showed good recovery. A good correlation to the Theradiag adalimumab ELISA was obtained for both serum (slope=0.94; r=0.99) and whole blood (slope=1.13; r=0.98) samples (Figure 1). Conclusion: Results indicate that the Procise ADL assay is sensitive, specific, and precise yielding results within 5 minutes from both whole blood and serum without the operator needing to specify sample type. Additionally, it shows good correlation to a comparator assay that takes several hours and sample manipulation to yield results. This makes the Procise ADL assay ideal for obtaining fast and accurate ADL quantitation, thus allowing for immediate drug level dosing decisions to be made by the physician during patient treatment.